Audit Quality, Leverage, and Financial Statement Quality: Evidence from the Consumer Cyclicals Sector - Khairani Nurhadiza; Hendro Lukman; Hendang Tanusdjaja (Politeknik Siber Cerdika Internasional, 2026)
Background: Financial reporting scandals in Indonesia have intensified scrutiny of audit quality as a safeguard for reporting integrity. Despite extensive audit reforms and mandatory rotation policies, empirical evidence on whether audit quality proxies such as tenure, delay, fees, and auditor specialization translate into higher financial statement quality remains inconclusive. Objective: This research was conducted to evaluate the influence of audit quality, as proxied by audit tenure, audit delay, audit fees, and auditor specialization, on the financial statement quality proxied by discretionary accruals, as well as to investigate whether leverage plays a moderating role in this relationship. Methods: The research sample comprises companies of the Consumer Cyclicals sector listed on the Indonesia Stock Exchange during the period 2022–2024. A total of fifty-three companies were selected using purposive sampling, representing 159 firm-year observations. A panel data regression method was employed using EViews 12 software. Results: The findings revealed that there is no effect of any independent variable on the quality of financial statement, both with and without leverage as a moderating variable. These results indicate that audit quality does not necessarily improve the quality of financial statement. The study uncovers many detrimental scenarios, implying that a strengthening of corporate governance and internal control systems should be viewed as necessary preconditions for reliable financial statement. Conclusion: The improvement of the quality of financial statement is not only determined by the quality of audits and the level of leverage, but also by the effectiveness of corporate governance and internal control systems.